Pengembangan LKPD Menulis Puisi dengan Pendekatan Stilistika - Ningsih, Komang Sri Rahayu; Wicaksono, Andri; Anggraini, Tri Riya (STKIP PGRI Bandar Lampung, 2022)
This study aims to develop a product of teaching materials in the form of LKPD, namely the Development of LKPD Writing Poetry with a Stylistic Approach. This study uses research and development methods by adapting the Jolly and Bolitho development model. For the feasibility of teaching materials, expert validation and limited field tests were carried out. Validation was carried out on the feasibility of presentation, material, and linguistics of the Indonesian Language and Literature Education Study Program STKIP PGRI Bandar Lampung. The data in the limited field test were obtained through a written test, namely a multiple choice test and a poetry writing test. Subjects in this field test consisted of 30 students of class X SMA Negeri 16 Bandar Lampung. The test results to identify elements of the form of poetry showed an increase from the average value of 55.00 to 81.50 (difference 26.50). The results of the poetry writing test also showed an increase from the average score of 64.60 to 80.90 (difference 16.30). Thus, the LKPD developed by researchers is suitable for use for class X SMA Negeri 16 Bandar Lampung students.